Rothberger's property in uniform spaces - Gouigah M.R.; Seba D. (University Of Eloued جامعة الوادي, 2020)
In this work, we introduce several equivalent concepts of uniform spaces then give the no- tion of selection principles in each one (Speci cally Rothberger-type property), and study some properties.
intervention
Keywords: selection principles; Uniform space; Rothberger-bounded; Weakly Rothberger-bounded